Budget reform: an evaluation of the implementation of performance budgeting in the Department of Health, Mpumalanga - Shall, Adrienne (School of Economics, 2023)
Due to the resource constraints faced by most governments, there is increasing recognition globally of the need to improve the efficiency and effectiveness of public service delivery. The budgeting system is a critically important tool with which to do this. Budget reform consists not only of reforming the resource allocation process, but goes much further to include reform of financial planning and management systems and processes of monitoring and evaluation. Even more crucial is the implementation process of budget reform: no matter how good a budgetary system has been developed, the test of the system is not in the design but in the implementation. This dissertation evaluates the implementation of budget reform within the Otief Directorate: Health in the Department of Health, Welfare and Gender Affairs of the Province of Mpumalanga. Chapter 1 sets out the rationale for the study. Chapter 2 reviews traditional budgeting and its limitations in terms of allocating resources for improved service delivery, and discusses the evolution and inadequacies of budgeting in South Africa. Chapter 3 is a theoretical review of the performance budgeting system, detailing its various components including strategic planning, financial planning, expenditure management, performance management and organisational design. Chapter 4 categorises issues concerning successful implementation of performance budgeting in terms of political, administrative/ bureaucratic and technical aspects. Chapter 5 describes the goals, objectives and organisational structure of the Otief Directorate: Health of Mpumalanga. The limitations of the previous budget process and structure are reviewed, highlighting the need for reform. Chapter 6 evaluates the implementation process of performance budgeting in the Chief Directorate: Health, describing the three conceptual phases of the process and focusing on the obstacles faced. Chapter 7 recommends the following for the successful implementation of performance budgeting: a detailed situational analysis to improve the understanding of the current situation and provide a common reference point; development of an implementation plan; personal involvement of top management; effective management of the process of transformation; documentation of the process as it unfolds; and development of management capacity at all levels.